2014
DOI: 10.1155/2014/167681
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Response FactorSl-ERF.B.3Is Responsive to Abiotic Stresses and Mediates Salt and Cold Stress Response Regulation in Tomato

Abstract: Sl-ERF.B.3 (Solanum lycopersicum ethylene response factor B.3) gene encodes for a tomato transcription factor of the ERF (ethylene responsive factor) family. Our results of real-time RT-PCR showed that Sl-ERF.B.3 is an abiotic stress responsive gene, which is induced by cold, heat, and flooding, but downregulated by salinity and drought. To get more insight into the role of Sl-ERF.B.3 in plant response to separate salinity and cold, a comparative study between wild type and two Sl-ERF.B.3 antisense transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…Annotation resulted in the putative participation of ZmERF in diverting the biological, cellular and chemical processes including abiotic stress responses like drought, cold, temperature, salinity etc. Our finding is similar to previous study of AP2/ERF genes in other species, like expression of PeDREB2 in Populus euphratica carried enhancement of drought and cold (Chen et al, 2009;Kumar and Venkateswarlu, 2011) and expression of Sl-ERF.B.3 gene in tomato was only observed under stress condition (Klay et al, 2014). The molecular process of ZmERF showed that all 105 genes have sequence-specific DNAbinding activity which is already reported as a feature of AP2/ERF gene (Yamasaki et al, 2013) and also studied in cucumbers (Hu and Liu, 2011).…”
Section: Gene Ontology Annotationsupporting
confidence: 92%
“…Annotation resulted in the putative participation of ZmERF in diverting the biological, cellular and chemical processes including abiotic stress responses like drought, cold, temperature, salinity etc. Our finding is similar to previous study of AP2/ERF genes in other species, like expression of PeDREB2 in Populus euphratica carried enhancement of drought and cold (Chen et al, 2009;Kumar and Venkateswarlu, 2011) and expression of Sl-ERF.B.3 gene in tomato was only observed under stress condition (Klay et al, 2014). The molecular process of ZmERF showed that all 105 genes have sequence-specific DNAbinding activity which is already reported as a feature of AP2/ERF gene (Yamasaki et al, 2013) and also studied in cucumbers (Hu and Liu, 2011).…”
Section: Gene Ontology Annotationsupporting
confidence: 92%
“…These data implies that TERF1 acts as a linker between the ethylene and osmotic responses coupling two pathways of responses (Huang et al 2004). Similarly, the analysis of Sl-ERF.B.3 (the ethylene response factor B.3 originating from tomato) revealed its engagement in response to a wide range of stresses, including flooding, heat, cold, drought as well as salinity (Klay et al 2014). Its expression is up-or downregulated by the aforementioned stresses.…”
Section: Transcription Factors (Tfs)mentioning
confidence: 76%
“…Reguera et al ( 2013 ) reported that phytohormone engineering, i.e., cytokinin, leads to increase drought tolerance in rice. Similarly, Klay et al ( 2014 ) reported that ethylene response factor leads to enhance salt and cold tolerance in tomato. Colebrook et al ( 2014 , for details, see review) reported that gibberellins (GA) have a signifi cant role in response to abiotic stress.…”
Section: Roles Of Phytohormones In Abiotic Stress Tolerancementioning
confidence: 90%
“…ET is a gaseous phytohormone and has been documented for its involvement in plant stress responses, in addition to its roles in germination, fruit ripening, organ abscission, pathogen, and senescence (Chen et al 2005 ;Klay et al 2014 ). There are various reports confi rming that the accumulation of ET or its precursor ACC (aminocyclopropane-1-carboxylic acid) is sharply induced by abiotic stress conditions such as soil salinity (Zapata et al 2007 ) and water stress (Narayana et al 1991 ).…”
Section: Genetic Engineering Of Ethylene Metabolismmentioning
confidence: 99%
See 1 more Smart Citation